INTERNALISALISASI NILAI-NILAI PENDIDIKAN ISLAM DALAM PEMBENTUKAN KARAKTER SISWA SDN IMPRES SAI - Aidin (STKIP Al-Amin Dompu, 2022)
Formal education in schools basically aims for every student to learn to live. Education is so important that it makes someone who lives in the community experience growth that is oriented towards the safety and happiness of life as high as possible. The research method used is the qualitative description, data collection techniques, observation, interviews, and documentation. The results of the study Internalization of Islamic values ​​in shaping the character of the class students of SDN Imppres Sai, Soromandi District, Bima Regency, namely every teacher has presented every learning material in all subjects, they always insert an emphasis on attitudes that have good values, social etiquette values, the development of values ​​and moral attitudes in students in behaving in students to always be done in their daily lives. In Islamic education in the classroom, there is a relationship between very close friendship, mutual openness, good social initiative as well as participation, and responsibility for the tasks given both in groups and independently carried out properly and on time.